Human Trafficking For Sexual Exploitation İn Malaysia: Issues And Solutions - Nafisah Ilham Hussin, Ahmad Miqdad Shamsuddin, Norhafiza Mohd Hed, Marshelayanti Mohamad Razali (International Journal of Advanced Science and Technology, 2020)
This study discusses human trafficking for sexual exploitation in Malaysia. It focuses on issues and solutions that have been undertaken by the Malaysian government in addressing the problem. In addition, this study analyses its implications on human and national securities. This study is based on qualitative research method, through an analysis on both, primary and secondary sources of data. The primary data were derived from interviews with the enforcement officers from Royal Malaysia Police, care and protection officer from Department of Women Development and victims of human trafficking for sexual exploitation at the detention camp (Rumah Perlindungan). The secondary data were gathered through online sources, documents, reports, statistical information from the official agencies, journals, books and newspapers that are related to the study. The findings of the research show that globalization is the platform for human trafficking and sexual exploitation in Malaysia. The constant demand for prostitutes helps to accelerate the ever expanding activity of this crime in Malaysia. The Malaysian government has been undertaking efficient efforts in addressing the issue through legal aspects, enforcement, custody and protection, media and publicity, as well as cooperation with foreign countries, but the problem is difficult to be eradicated completely due to the various obstacles that need to be addressed from time to time.